1989
DOI: 10.1039/f19898502499
|View full text |Cite
|
Sign up to set email alerts
|

Intermicellar interactions and micelle size distribution in aqueous solutions of polyoxyethylene surfactants

Abstract: Mutual diffusion coefficients (D) and self-diffusion coefficients (D') in D,Osolutions of n-dodecylpolyoxyethylene surfactants [C,,H,,(OC,H,),OH, m = 5 and 81 have been measured by dynamic light scattering and pulsedgradient F.t.n.m.r., respectively. On the basis of the ratio DID', micelle size distribution and intermicellar interactions have been discussed. The results have been compared with those for the C12E, system reported previously. Below ca. T,-30 "C (T, is the lower critical solution temperature) siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 4 publications
1
29
0
Order By: Relevance
“…This has been confirmed by dynamic light scattering [34] and small angle neutron scattering [35]. NMR studies in such systems are expected to show considerable line broadening due to slow tumbling [36].…”
Section: Nmr Studiesmentioning
confidence: 51%
See 1 more Smart Citation
“…This has been confirmed by dynamic light scattering [34] and small angle neutron scattering [35]. NMR studies in such systems are expected to show considerable line broadening due to slow tumbling [36].…”
Section: Nmr Studiesmentioning
confidence: 51%
“…From 1 H NMR spectra, self-diffusion and proton relaxation studies, it has been shown that with increasing surfactant concentration C 12 E 5 forms elongated rod-like micelles [33,34]. This has been confirmed by dynamic light scattering [34] and small angle neutron scattering [35].…”
Section: Nmr Studiesmentioning
confidence: 62%
“…The data shows that R H of pure C 12 E 10 solutions remain nearly constant upto ∼35 • C, after which R H starts to increase due to the temperature increase. This response is typical of C i E j surfactants, and the measured apparent R H increase has been attributed to the onset of intermicellar attraction 47,[60][61][62] resulting from dehydration of the ethoxylate chains. Samples con- taining hexanol show similar overall behaviour to pure C 12 E 10 solution, but the onset of temperature induced increase in R H shifts to progressively lower temperatures (see Electronic Supplementary Information Figure S1).…”
Section: Resultsmentioning
confidence: 75%
“…[2], [A10], previous studies (10,11) at around the critical composition, it was shown that repulsive interactions (excluded volume effects) are dominant (k 2 ú 0) below about T c 0 4 K. Above this temperature, intermicellar interactions are dominated by attraction (k 2 õ 0). This conclusion is supported by direct measurements of the surface force on the C 12 E 5 system (40) and precise measurements of static and dynamic light scattering at the critical composition on the C 12 E 6 system (38).…”
Section: Effects Of Intermicellar Interactionsmentioning
confidence: 98%
“…Most of nonionic surfactant aggregation number), N A is Avogadro's number, M 1 is the systems have the lower critical solution temperature (T c ) molecular weight of the surfactant monomer, N w is the and the problem concerning attractive interactions between weight averaged aggregation number of micelles (see Eq. micelles or the critical effects led to debate on micellar [A12]), and c and c 1 are the weight concentrations in g growth with increasing temperature (10,11,(37)(38)(39). In our cm 03 ) of total surfactant molecules and surfactant monomers, respectively.…”
Section: Effects Of Intermicellar Interactionsmentioning
confidence: 99%